The Fundamental Groups of m-Quasi-Einstein Manifolds. (10th April 2012) - Lee, Hee Kwon
Abstract : In Ricci flow theory, the topology of Ricci soliton is important. We call a metric quasi-Einstein if the m -Bakry-Emery Ricci tensor is a constant multiple of the metric tensor. This is a generalization of gradient shrinking Ricci soliton. In this paper, we will prove the finiteness of the fundamental group of m -quasi-Einstein with a positive constant multiple.